Efektivitas Kebijakan Moneter Dalam Mengendalikan Inflasi di Indonesia - I’in Nur Khotimah; Muhammad Ahsanul Imam; Rini Puji Astuti (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effectiveness of monetary policy in controlling inflation in Indonesia and to identify the factors influencing the success of these policies. The method used is a literature review with a qualitative descriptive approach, examining relevant literature on monetary policy instruments such as benchmark interest rates, open market operations, reserve requirement ratios, and discount rates. The results show that Bank Indonesia’s monetary policy significantly contributes to maintaining price stability through regulating money supply and interest rates. However, structural challenges such as fluctuations in food prices and limited financial access in remote areas hinder the policy’s effectiveness. This study recommends the need for synergy between monetary policy, structural policies, and fiscal policies to maintain sustainable economic stability.